Are Tahiti Limes Profitable in South Florida? A Deterministic and Stochastic Budget Analysis - Ballen, F.H.; Blare, T. (Informa UK Limited, 2023)
Tahiti limes were an important fruit tree crop in South Florida until the late 1990s. Several factors contributed to the demise of the Florida lime industry, namely the impact of hurricane Andrew in 1992 and the arrival of Citrus Canker (CC) in 1995. The Florida lime industry was then eradicated in the early 2000s to protect the main commercial citrus industry from CC. This article focuses on the financial viability of reintroducing Tahiti lime production in South Florida. A total of 20 Tahiti lime scion/rootstock combinations were evaluated under endemic CC and Citrus Greening (CG) conditions. We created a deterministic and a stochastic budget to evaluate the feasibility of reintroducing Tahiti limes in South Florida that incorporated yields from experimental plots. We also implemented a financial analysis, that included net present value (NPV) and internal rate of return (IRR) estimations, for a 20-year period with the Tahiti lime/citrus macrophylla (TL/CM), the best performing scion/rootstock combination. Our findings indicated that Tahiti lime production in South Florida was not financially feasible; we obtained a negative NPV from both the deterministic and stochastic budgets. We conclude with a discussion of potential scenarios for the Tahiti lime industry in the US and on lessons for other crops that face similar production challenges.